Single and Sequential Herbicide Treatments for Efficacy in Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2020)
In this study, herbicides were tested to compare application of single and sequential treatments for weed control in corn. Quinoa and Russian thistle control was 95% or more regardless of herbicide treatment. Anthem Maxx, Resicore, and Corvus followed by Harness Max provided good control of Palmer amaranth. Acuron applied preemergence and Anthem Maxx plus Callisto and atrazine early postemergence were less effective on kochia than other herbicides, whereas Anthem Maxx plus Callisto and atrazine applied preemergence and Halex GT applied early postemergence were less effective on green foxtail. Grain yields from all herbicide-treated corn were substantially greater than for the nontreated control plots.
Keywords: residual control; split applications